Pengetahuan dan Minat Petani Sawit Berpartisipasi dalam Program Peremajaan Sawit Rakyat di Kabupaten Sanggau (Jurnal Agribisnis Indonesia, 2025)
Palm oil is one of Indonesia's main exports that brings in a significant amount of foreign exchange. Oil palm farmers face challenges in maximizing their productivity due to a lack of knowledge and interest among farmers in replanting oil palms. Currently, there are still many smallholder plantations that are more than 25 years old but have not been replanted due to lack of replanting costs and farmers do not have a replacement income when the oil palm is replanted. Smallholder oil palm rejuvenation (PSR) is replacing old plants with new, more productive plants with certified superior seeds and is expected to benefit farmers. This research was conducted in Sanggau District, with 100 respondents of oil palm farmers who have replanted, especially in Parindu and Kapuas Sub-districts which are the centers of oil palm plantations. This research uses purposive sampling method (certain considerations) and sequential/stage mixed research method, especially sequential explanatory strategy because it focuses on quantitative data and qualitative data as supporting data. The research aims to see how much the knowledge and interest of the community influence participation in community oil palm replanting. Knowledge theory and interest theory complement each other to form a comprehensive management system or operational system in handling community oil palm replanting from an external and internal perspective. Knowledge and interest have a positive and significant influence on decision-making. The results show that knowledge and interest complement each other and have a strong influence on participation. Good financial management is the key to success and helps farmers improve their farming business because every farming activity requires capital. Knowledge needs to be improved by providing training according to the needs of farmers.